Analysis of Some Meteorological Data and Their Variation Trends in Three Provinces of the Western Black Sea Region Between 2012 and 2021 - Bolat, İlyas; Şensoy, Hüseyin; Bolat, İlyas; Şensoy, Hüseyin (Aves, 2023)
Many recent studies report that the world has been warming on a local, regional, continental, and global scale with an increase in extreme precipitation and temperatures, posing serious risks. This study was carried out in three provinces located in the Western Black Sea region for the purpose of identifying regional changes in some climatic parameters including monthly minimum, average and maximum temperatures, and monthly average minimum, maximum, and total annual precipitation in the last decade (2012-2021). The provinces in the study include Bartin, Zonguldak, and Duzce. The year with the highest average temperature was 2018 in Bartin (14.39 degrees C), 2019 in Zonguldak (15.47 degrees C), and 2018 in Duzce (15.35 degrees C). The results of the simple linear regression model indicated an increasing trend in the average minimum and maximum temperature and the annual average temperature in all three provinces (Bartin; r =.568, Zonguldak; r =.653, Duzce; r =.584). The regression analysis performed to identify the variation in the average total precipitation over the years revealed that the average total precipitation had a decreasing trend in Bartin (r = -.081) yet an increasing trend in Zonguldak (r =.423) and Duzce (r =.306). The study results suggest that, on a regional scale, the temperatures tend to increase, whereas the regime and distribution of precipitation show variation. Considering these results, the Western Black Sea region is at risk of global warming and has strong signals of this risk.
Analysis of Some Meteorological Data and Their Variation Trends in Three Provinces of the Western Black Sea Region Between 2012 and 2021
Keywords: Precipitation; Regression Model; Temperature; Variation Trend; Western Black Seaprecipitation; Regression Model; Temperature; Variation Trend; Western Black Sea